Frequent shifts in Aspergillus flavus populations associated with maize production in Sonora, Mexico - Ortega Beltran, A.; Cotty, P.J. (Scientific Societies, 2018)
Aspergillus flavus frequently contaminates maize, a critical staple for billions of people, with aflatoxins. Diversity among A. flavus L morphotype populations associated with maize in Sonora, Mexico was assessed and, in total, 869 isolates from 83 fields were placed into 136 vegetative compatibility groups (VCGs) using nitrate-nonutilizing mutants. VCG diversity indices did not differ in four agroecosystems (AES) but diversity significantly differed among years. Frequencies of certain VCGs changed manyfold over single years in both multiple fields and multiple AES. Certain VCGs were highly frequent (>1%) in 2006 but frequencies declined repeatedly in each of the two subsequent years. Other VCGs that had low frequencies in 2006 increased in 2007 and subsequently declined. None of the VCGs were consistently associated with any AES. Fourteen VCGs were considered dominant in at least a single year. However, frequencies often varied significantly among years. Only 9% of VCGs were detected all 3 years whereas 66% were detected in only 1 year. Results suggest that the most realistic measurements of both genetic diversity and the frequency of A. flavus VCGs are obtained by sampling multiple locations in multiple years. Single-season sampling in many locations should not be substituted for sampling over multiple years.